Gen-X to Zoomers: a systematic review on intergenerational digital tensions during digitalisation - Umar Baki, Nordahlia; Mohd Yusri, Ahmad Baihaqie (Macrothink Institute, 2024)
This systematic literature review aims to explore the growing intergenerational digital tensions between Gen-X, Millennials, and Zoomers in the workplace, particularly during periods of rapid digitalization. As technology, particularly artificial intelligence (AI), becomes more integrated into business operations, generational disparities in perspectives of digital tools cause friction. While newer generations, such as Millennials and Zoomers, are eager to adopt new technologies, Gen-X is more cautious, frequently expressing concerns about the risks and long-term ramifications of digital tools. The review looks at key themes including psychological empowerment, communication styles, and workplace collaboration, and shows how economic pressures and social media worsen generational gaps. Additionally, the paper emphasizes the role of tailored training programs and organizational interventions in mitigating these tensions and fostering an inclusive digital ecosystem. By consolidating research across various studies, the review provides critical insights into how organizations can bridge these generational gaps to achieve successful digital transformation. Ultimately, this research highlights the importance of understanding and addressing intergenerational dynamics in the digital workplace to enhance collaboration, efficiency, and adaptability especially during the integration of advanced technologies.